Reconstruction of the Old Bydgoszcz Canal buried section as a potential direction for development of green and blue infrastructure in Bydgoszcz city center - Mechkin, Karl (Ecological Questions, 2023)
This paper tackles the possibility for the reconstruction of the buried section of the Old Bydgoszcz Canal, as a potential direction for the development of green and blue infrastructure in Bydgoszcz city center. As a result of the literature review, archival query, field works, and social research in the form of a public survey and interviews with local experts, the concept for reopening the buried section of the Old Bydgoszcz Canal was drawn up. It takes into account local spatial conditions and social expectations and shows how the project complies with the current municipal strategic and planning documents. This work also presents historic and contemporary practices for the development of urban water areas, and concepts of ecosystem services, climate change adaptation, and urban quality of life, which are important for the development of urban green infrastructure. The results of this research lay the foundations for a broader discussion on the possible reconstruction of the Bydgoszcz Canal, as well as the implementation of similar projects in other cities.